(untitled) (International Journal of Mathematics and Physics, 2013)
The use of natural eco-friendly energy, such as wind, due to the use of wind energy devices [1-3]. This thesis is a theoretical study of the interaction of the rotating turbine Darrieus-type H-rotor wind flow. The paper considers the interaction of a uniform wind flow with a rotating wind turbine Darrieus-type H-rotor, based on the Navier-Stokes equations, which is supplemented by members which take into account the lift and the drag force. The numerical solution of the equations in the variables u-v-p. The results obtained and the development of his methods of analysis will be useful for the design work for the creation of industrial designs windmill carousel.